The Role of Stakeholders in the Efficiency of Nonprofit Sports Clubs - Miragaia, D. A. M. (2020)
This article analyzes the efficiency levels of nonprofit sports clubs through the data envelopment analysis methodology and specifically evaluates how efficient and inefficient clubs perceive the distinct contribution of stakeholders in attaining their respective levels of output efficiency. The results distinguish the varying levels of efficiency between such clubs and highlight significant differences in the roles of the local government and of associations and federations in attaining these efficiency levels. The study further suggests best practices that can be adopted by officials at inefficient clubs toward reducing or eliminating their shortfalls in efficiency.